Form follows function: in pursuit of solutions to the unresolved issues of the benefit-sharing regime for marine genetic resources under the BBNJ agreement - Yu, Wenlong; Tang, Yi; Sun, Yuqiong; Zhang, Yanxuedan (Frontiers in Marine Science, 2025)
While the Agreement under the United Nations Convention on the Law of the Sea on the Conservation and Sustainable Use of Marine Biological Diversity of Areas Beyond National Jurisdiction (BBNJ Agreement) has pioneered the establishment of a benefit-sharing regime for marine genetic resources (MGRs), persistent divergences between developing and developed countries have posed substantial challenges to its implementation. The current legal framework is overly schematic and insufficient to guide practice, leaving many issues unresolved. To explore the solutions for these issues, this article adopts a legal functionalist approach grounded in the principle that “form follows function”. First, this article categorizes the unresolved issues into four types: ambiguous terms in the Agreement, uncertain legal nature of benefit-sharing modalities, weak operability resulting from incomplete guiding rules, and inadequate monitoring rules. Second, it derives potential solutions from a legal functionalist perspective. This approach emphasizes the instrumental value or functionality of law. By focusing on facilitating the achievement of the Agreement’s intended functions and goals, this approach can help steer ongoing international rule-making activities and overcome negotiation deadlocks. Under such an approach, the core guiding principle for problem solving is to make rules operational by addressing conflicts, giving due regard to diverse concerns, and fostering broad consensus among negotiating parties. Finally, this article tentatively applies this approach to specific unresolved issues, including: adopting broader definitions of key terms; designing relatively light monetary benefit-sharing rules that combine mandatory and voluntary mechanisms; facilitating ex situ access through multilateral mechanisms; clearly delineating the respective scope of application of different technology transfer modalities; and strengthening supporting information disclosure and traceability rules. Concurrently, this article suggests that the design and implementation of rules should take into account the needs of marine scientific research, data confidentiality, financial and administrative burdens, and the legitimate rights and interests of stakeholders.